2022
DOI: 10.1021/acsabm.2c00239
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Secondary Structure and Assembly of Proteins on Fluoride Ceramic (CeF3) Nanoparticle Surfaces

Abstract: Fluoride nanoparticles (NPs) are materials utilized in the biomedical field for applications including imaging of the brain. Their interactions with biological systems and molecules are being investigated, but the mechanism underlying these interactions remains unclear. We focused on possible changes in the secondary structure and aggregation state of proteins on the surface of NPs and investigated the principle underlying the changes using the amyloid β peptide (Aβ 16–20 ) based on infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…With the increase of β‐sheet, the structure of the protein fiber will be more solid 37,38 . The addition of CeO 2 NPs directly increases the content of β‐sheet 39 and improves the mechanical properties of RSF fibers (Figure 4f).…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of β‐sheet, the structure of the protein fiber will be more solid 37,38 . The addition of CeO 2 NPs directly increases the content of β‐sheet 39 and improves the mechanical properties of RSF fibers (Figure 4f).…”
Section: Resultsmentioning
confidence: 99%
“…The potential for such conformational changes was indicated by the Raman shift in the amide I region of bovine serum albumin (BSA) interacting with zinc oxide NPs ( Žūkienė and Snitka, 2015 ). Based on the Fourier transform infrared (FT-IR) spectra of the amide I band ( Sakaguchi et al, 2022 ), we recently reported that concentrating amyloid β peptides on the NP surface may enhance the formation and stacking of their β-sheet structure. The coexistence of ions that can interact with peptides also modifies the interaction between the NPs and peptides ( Sakaguchi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Fourier transform infrared (FT-IR) spectra of the amide I band ( Sakaguchi et al, 2022 ), we recently reported that concentrating amyloid β peptides on the NP surface may enhance the formation and stacking of their β-sheet structure. The coexistence of ions that can interact with peptides also modifies the interaction between the NPs and peptides ( Sakaguchi et al, 2022 ). Some other studies reported a potential of secondary structure (conformational) changes of albumin by metal oxide NPs such as titanium dioxide, zinc oxide, CeO 2 , ( Simón-Vázquez et al, 2014 ; Ranjan et al, 2016 ; Bukackova and Marsalek, 2020 ), and iron oxide ( Mehrabi et al, 2021 ; Nisar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%